A lexical-semantic analysis of Anthony Burgess's a clockwork orange - Solis, Mildred Alcano
This research paper explores the relationship between semantics and the lexical formations and processes in a literary text. It applies the lexical-semantic theory of Michael Cummings and Robert Simmons to the novel, A Clockwork Orange by Anthony Burgess. This paper likewise presents the lexical unions and colligations that are present in the Nadsat language, or the invented lexicon of burgess in the novel.